2002
DOI: 10.1093/gerona/57.7.m414
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Use of Statins on the Prevalence of Dementia and the Progression of Cognitive Impairment

Abstract: The use of statins is associated with a lower prevalence of dementia and has a positive impact on the progression of cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
4
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(102 citation statements)
references
References 29 publications
2
94
4
2
Order By: Relevance
“…HDL in this cohort of middle age women was not associated with memory [34]. Others have noted that the use of HMG-CoA-reductase inhibitors (statins) is associated with a lower prevalence of dementia [35]. However, as the authors pointed out, there may be a selection bias influencing the observed relationship, since statins may be less likely to be prescribed to patients with dementia [35].…”
Section: Comorbiditiesmentioning
confidence: 64%
See 1 more Smart Citation
“…HDL in this cohort of middle age women was not associated with memory [34]. Others have noted that the use of HMG-CoA-reductase inhibitors (statins) is associated with a lower prevalence of dementia [35]. However, as the authors pointed out, there may be a selection bias influencing the observed relationship, since statins may be less likely to be prescribed to patients with dementia [35].…”
Section: Comorbiditiesmentioning
confidence: 64%
“…Others have noted that the use of HMG-CoA-reductase inhibitors (statins) is associated with a lower prevalence of dementia [35]. However, as the authors pointed out, there may be a selection bias influencing the observed relationship, since statins may be less likely to be prescribed to patients with dementia [35]. Another study examining the impact of plasma lipids on memory performance in healthy elderly individuals found no association between changes in cognition and plasma triglycerides, LDL or treatment with lipid lowering agents [36].…”
Section: Comorbiditiesmentioning
confidence: 99%
“…This may be an effect of the treatment of hypercholesterolemia with statins. Studies have shown that the use of statins can reduce the risk of the onset of dementia, and is correlated with a reduced prevalence of dementia (Haag et al 2009;Hajjar et al 2002). Furthermore, the use of statins has been shown to delay the progression of cognitive impairments (Hajjar et al 2002), and therefore to reduce the risk of LTC among patients with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Podobno je dokazal tudi Hajjar s sodelavci (76), ki je raziskoval povezavo med uporabo statinov in prevalenco demence ter vpliv statinov na napredovanje kognitivnega upada. Ugotovil je, da je raba statinov povezana z nižjo prevalenco demence in upočasnjuje upad spoznavnih sposobnosti.…”
Section: Vpliv Povišanih Maščobunclassified